An Exploratory Analysis of Supply Chain Contract on Efficiency, Simulation, and Data analytics Augmentation Technologies - Heilala, Janne (Journal of Advanced Management Science, 2025)
The European Manufacturing Survey 2022 (EMS22) evaluated the Finnish manufacturing industries between advanced manufacturing technologies and sustainability management systems in Finnish industrial companies. The profitability was compared under the Development of Competitiveness and Employment Situations (DCES) narrowed industry requirements. The study utilized EMS22 techno-organizational innovation indicators to measure performance components within manufacturing organizations. In the first part, the horizontal factors were considered thoroughgoingly with a literature review: significant growth in the Finnish industry between 2014-2018, the impacts of the COVID-19 pandemic, and the importance of integrating sustainable practices in manufacturing operations. In the second part, the EMS22 larger pool of respondees provided parities in statistical assumptions on a national scale. The implications of Supply Chain Contracts (SCC) on manufacturers and contract manufacturers were assessed in diverse Human Resources (HR) contexts by comparing the firms’ employee percentages. The findings highlight the critical role of adopting Efficiency Technologies (ET) and simulation, data analysis, and additive manufacturing technologies to enhance firms’ competitiveness in augmenting virtual and reality. Conversely, to expectations, companies were lagging in advanced technology adoption, particularly needing a focus on university resources-driven innovations. Firms lacking certified environmental management systems demonstrated reduced competitiveness. The survey underlines the importance of energy management systems for firms’ satisfactory performance. The future of research is headed for the determinants of competitiveness on a national scale by integrating business and artificial intelligence into sustainability strategies among exploring sustainable manufacturing.